2010
DOI: 10.1007/s00284-010-9794-z
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Secreted Laccase Activity in the Edible Fungi and their Growing Cycles are Closely Related

Abstract: This article focuses on the relation between laccase-secreting ability and growing cycle in the edible fungi. First, laccase activities of fifteen different edible fungi were detected and determined by plate assay and spectrophotometric method using 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) as the substrate. The results showed the laccase-secreting ability in the edible fungi and their growing cycles are closely related. The edible fungi strains with short growing cycles originate from their high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…Laccases are directly involved in lignin bioconversion in A. bisporus and L. edodes (Ohga et al, 1999;Ohga and Roys, 2001); The levels of laccases secreted by edible fungi are also closely related to production cycles, with heightened laccase secretion levels in fungi with short growth cycles (Sun et al, 2011). Laccase activities and production can be induced by various factors during fungal growth (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Laccases are directly involved in lignin bioconversion in A. bisporus and L. edodes (Ohga et al, 1999;Ohga and Roys, 2001); The levels of laccases secreted by edible fungi are also closely related to production cycles, with heightened laccase secretion levels in fungi with short growth cycles (Sun et al, 2011). Laccase activities and production can be induced by various factors during fungal growth (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, laccase has been developed as a novel screening marker in mushroom breeding (Sun et al, 2014). The levels of secreted laccase activity in edible mushrooms and their growing cycles are closely related, and short growing cycles are accompanied by high laccase activity (Sun et al, 2011). …”
Section: Natural Laccase Producersmentioning
confidence: 99%
“…Group II had middle level of cultivation periods, and group III had the longest cultivation periods among all groups. The strains in group I, group II or group III also showed different cultivation periods (Pang et al ., 2003; Zhang, 2003; Sun et al ., 2011). The results showed that LiP-secreting and MnP-secreting capacity and variety of mushroom are closely related to cultivation period.…”
Section: Resultsmentioning
confidence: 99%
“…a−: colour of mixture has no change; +, ++, +++: colour of mixture is changed more and more quickly.bReferences [1], [2] and [3] are Sun et al ., 2011, Zhang, 2003 and Pang et al ., 2003 respectively, and the cultivation periods refer to the industrial production.ACCC, Agricultural Culture Collection of China; LDFs, litter-degrading fungi; WRFs, white-rot fungi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation